STRUCTURAL LANDSLIDES IN PYIHA RIVER BASIN (EASTERN CARPATHIANS) - SHEVCHUK, V.; IVANIK, O.; HUDA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The complex geological situation and conditions of the landslide processes in Golubune (Zakarpatskaya area) based upon detail data of the field work and special analytical research are considered. The structure and position of the subparalel destructive sructural zones related to river valleys has been characterized. The main factors of landslide formation have been considered. Priority role of structure-destructive processes in the landslide formation has been proved.